Measurements of cardiac efficiency and internal work of the left ventricle via reconstructed impedance cardiography. (9th April 2021) - Kuang, Shi-Jiang; Xiao, Qiu-Jin; Kuang, Ming-Xing; Zhao, Hui; Li, Bing; Dong, Li-Qiang; Ruan, Ying-Lan
Abstract: Objective . The aim of this study was to investigate methods for measuring the cardiac efficiency (CE) and internal work (IW) of the left ventricle via reconstructed impedance cardiography (RICG). Approach. On the basis of the physiological context and Bernoulli's equation in physics, methods of measuring the CE and IW were proposed. The CE, IW, internal work index (IWI), and other data from 180 healthy adults and 144 patients with cardiovascular disease were measured. Main results . The CE of 180 healthy adults was 22.5 ± 2.2%, and the IWI was 22.3 ± 5.2 J l −1 m −2 . CE decreased with age, and the CE of the younger group (23.5 ± 1.9%) was larger than that of the older group (21.5 ± 1.9%), P < 0.01. The IWI increased with age, and the IWI of the younger group (19.0 ± 3.8 J l −1 m −2 ) was smaller than that of the older group (24.8 ± 4.3 J l −1 m −2 ), P < 0.01. There were no significant difference in CE (22.4 ± 2.2% and 22.6 ± 2.2%) or in the IWI (21.9 ± 5.1 J l −1 m −2 and 22.6 ± 5.2 J l −1 m −2 ) between the male and female groups. The CEs and IWIs of patients with hypertension, coronary heart disease, and heart failure were 17.4 ± 2.4% and 41.8 ± 15.6 J l −1 m −2, 17.6 ± 3.0% and 35.1 ± 10.4 J l −1 m −2, and 15.8 ± 3.5% and 42.1 ± 15.6 J l −1 m −2, respectively. These CEs were all smaller than that (21.6 ± 2.0%) of the healthy contrast group P < 0.01, while the IWIs were all larger than that (24.6 ± 4.8 J l −1 m −2 ) of the healthy contrast group, P < 0.01. Significance. The CEs and IWIs measured in this study may reflect physiological changes in healthy humans and pathogenic conditions in patients with cardiovascular disease.